Pengaruh Pemberian Buah Beri Kaya Antosianin Terhadap LDL pada Manusia : Meta-Analisis Uji Coba Terkontrol Acak - Destriana Putri Ayu Ningtyas (Lembaga Pengembangan Kinerja Dosen, 2025)
Cardiovascular disease especially coronary heart disease (CHD) and stroke, is the main cause of global death, with increased blood lipid levels as one of the risk factors. This research offers the potential of anthocyanin-rich berry supplements in reducing low-density lipoprotein cholesterol (LDL-C) levels and improving blood lipid profiles through a meta-analysis of randomized controlled trial studies (RCTs). Data was collected from various databases and filtered based on inclusion and exclusion criteria. Analysis shows that consumption of berry supplements containing anthocyanins can reduce LDL-C levels by 0.29 mmol/L compared to the control group, with a p value <0.05 and I2 = 79%, indicating that the variation between these studies is heterogeneous. These findings are in line with previous research which showed a 13.6% reduction in serum LDL-C levels in the group consuming anthocyanins. In the whortleberry exposure group, the results showed that of the two journal articles analyzed, the data points fell outside the confidence interval (CI), indicating there was no significant difference in the results of the studies. The use of anthocyanins on berries other than whortleberries showed a significant effect, while on whortleberries, the difference with or without anthocyanins was not significant. The results of this study emphasize the importance of consuming anthocyanin-rich berry supplements in improving blood lipid profiles and reducing the risk of cardiovascular disease, and support the development of anthocyanin-based nutritional supplements as an effective public health strategy.